WRITING PROCEDURE TEXT BY USING TEAM PAIR SOLO TECHNIQUE - Nabujing, Nurul Hidayah; Utari, Putri (English Education Study Program FKIP Universitas Alwashliyah Medan, 2023)
This article elaborate the teaching of writing procedure text by using team pair solo technique. The steps or procedures of using this technique are described thoroughly. This technique can be one option for the teachers to assist them in teaching learning writing of English.